Reproductive characteristics of Nemipterus peronii (Valenciennes) from the East Coast of Peninsular Malaysia - Mohd Said, Mohd Zaki; Mohammad Mohsin, Abu Khair; Ambak, Mohd Azmi (Universiti Putra Malaysia Press, 1994)
Sampling for N. peronii was conducted monthly on the East Coast of Peninsular Malaysia using a trawler. From a sample size of 3608 individuals, it can be deduced that the success of N. peronii is due to its reproductive characteristics. Females predominate the population at small sizes while males at larger sizes. This study indicates the existence of sex-specific differences in growth, with males growing faster than females. Wide variation in fecundity, associated with spawning frequency was also observed. The data indicated an annual cycle of reproductive activity with the peak activity occurring early in the year.